Custo-efetividade da terapia compressiva no processo de cicatrização de úlceras venosas - Bezerra, Eurides Araujo (2009)
Analytical study of therapeutic nonrandomized intervention type, intra-group controlled, with the aim of analyzing the cost-effectiveness of compression therapy with manipulated Unna boot in relation to conventional therapy in the healing of venous ulcers (VU) of patients treated in ambulatory clinic. The study population was composed by patients with VU treated by angiologists in Surgical Clinic Ambulatory of the Onofre Lopes University Hospital (HUOL) with a sample of 18 patients. It obtained the assent of the HUOL Ethics in Research Committee (Protocol 276/09). Data collection was performed over a period of four months by the own master's student and 34 nursing students, through the application of the research instrument in the admission of patients to the study and in the ten subsequent evaluations, performed at the time of changing Unna boot, weekly, for a maximum period of 10 weeks. The data were analyzed with SPSS 15.0 software, using descriptive and inferential statistics, and presented as tables, charts and graphs. Among those surveyed, prevailed: females, mean age 57.6 years, low education and income levels, most retired, unemployed or off work, with the standing position more than six hours per day and up to eight hours daily of domestic or occupational activities. In health status profile of respondents there were predominantly sleep, rest and inadequate elevation of the lower limbs, no smoking and/or alcohol use, presence of hypertension and no use of drugs. Most presented the first VU for over 10 years, recurrences, present VU for more than five years, involvement of left leg, in malleolar and / or distal leg region, mild edema, hyperpigmentation, lipodermatosclerosis, telangiectasies, reticular and varicose veins, mild pain, serous exudate in moderate quantity, small lesions (up to 50cm2), with predominance of granulation tissue and / or epithelialization and demarcated, elevated and irregular borders, with crusts and macerated. Most patients reported that in the 10 weeks prior to admission, made bandages at home and / or Basic Health Unit and / or ambulatory, with nursing aides or technicians, daily, and on weekends or holidays, performed by patients themselves, using healing ointment on the lesion, being observed granulation / epithelialization and increase in VU prevalent in the 10 weeks of traditional treatment. After follow up with manipulated Unna boot, was observed a decrease of lesions in all study patients, with complete healing in 27.8% of those between 1 and 5 weeks of treatment, with satisfactory evolution of the lesions, pain and ankle and calf circumferences, and unsatisfactory development of the borders of ulcers, edema, sleep, rest and elevation of the lower limbs, especially in more chronic patients. Furthermore, patients who achieved total healing and exhibited the greatest percentage reduction of lesions had a higher number of wound healing factors (ρ = 0.01 and ρ = 0.027, respectively). The manipulated Unna boot showed better results in those patients with shorter duration of injury, leading them to a satisfactory outcome within a short period of treatment. After the cost-effectiveness analysis, we conclude that the manipulated Unna boot is more effective than conventional therapy in the healing process of VU and is more cost-effective in patients with shorter lesions (ρ = 0.001), shorter treatment (ρ = 0.000) and greater number of wound healing factors (ρ = 0.005).